Personal branding through leadership - Milovanovic, Svetislav; Baltezarevic, Borivoje; Milovanovic, NIna (International Review, 2016)
The main idea of this study is to demonstrate that leadership is increasingly becomingan important and current global phenomenon known as personal branding. Leadership is ofutmost importance for each human activity, and even for the entire progress of humanitywhich has always moved forward thanks to people and, naturally, great endeavors of greatpeople. Leadership is what makes the world go round. Although a personal brandinginvestigated in terms of defining, describing various practices and the growing importanceof the use of these techniques, there is still a gap in the scientific literature regarding howtechnology advancement in the business to take advantage of the positioning of theindividual in the global market. Therefore, the primary objective of this paper provide newinsights into the personal branding that will be useful for the academic community andprovide conclusions for its practical application in entrepreneurship.